Can Climate Defence be Evaluated within the Scope of State of Necessity?: An Evaluation in the Light of the Decisions of the US, German and Swiss Courts - Ezgi Çırak Karalı (Ceza Hukuku ve Kriminoloji Dergisi)
To draw public attention to the negative effects of climate change and global warming and mobilize official decision-making bodies, the creative but unlawful actions of climate protesters have recently attracted attention. Actions such as blocking the main roads of the city to draw attention to the damage caused by fossil fuels, sit-down strikes and even gluing themselves to the road, throwing soup at priceless artifacts in museums, and sticking their hands on the maestro’s desk during a symphony concert, however remarkable they may be, are criminal offenses. Indeed, protesters face criminal proceedings for their actions. In these criminal proceedings, the protesters claimed that they had carried out a proportionate attack to prevent a grave and imminent danger to the environment and argued that their actions should be regarded as acts of necessity. In this study, the arguments in the doctrine in favor of and against the protesters’ arguments are examined; the decisions of the US, German, and Swiss courts are evaluated, and a general evaluation is made on whether the protesters should be punished or not.